Public debt in India Moving towards a prudent level? - Joumard, Isabelle (OECD Economics Department Working Papers, 2017)
In relation to GDP, India's public debt and interest payments are high compared with most other emerging economies and rating agencies have put India's sovereign debt at the lowest investment grade. On the other hand, India benefits from strong economic growth and needs to increase spending on social and physical infrastructure to support economic growth and to meet the needs of its fast-growing population. This paper assesses recent fiscal developments in India, discusses the threshold beyond which debt has adverse effects on the economy, quantifies the uncertainties surrounding key macroeconomic variables and the risks of overshooting the debt threshold to define a "prudent" debt level. It also provides a debt sustainability analysis. It concludes that under a "no-policy change" scenario, the debt-to-GDP ratio will decline gradually to close to the "prudent" level by 2040. However, adverse shocks could derail this benign scenario